Assessment of seminal mast cells in infertile men with varicocele after surgical repair. (1st June 2016) - Mostafa, R. M.; Abol‐Magd, R.; Younis, S. E.; Dessouki, O. F.; Azab, M.; Mostafa, T.
Summary: This study aimed to assess seminal mast cells in infertile men associated with varicocele (Vx) pre‐ and post‐surgical repair. Forty‐five infertile men associated with Vx were subjected to history taking and clinical examination. In addition, semen parameters and seminal mast cells stained with 1% toluidine blue were estimated pre‐varicocelectomy and three months post‐varicocelectomy. Vx surgical repair revealed a significant improvement in the mean sperm concentration, progressive sperm motility, total sperm motility and sperm abnormal morphology and a significant decrement in seminal mast cells (mean ± SD, 3.56 ± 2.23 cells per high‐power field (HPF) vs. 2.22 ± 1.06 cells per HPF, p = .01). The pre‐operative mean mast cell count demonstrated significant increases in cases with Vx grade III compared with other Vx grades and in cases with bilateral Vx compared with unilateral Vx cases. Seminal mast cells demonstrated a significant correlation with sperm concentration, progressive sperm motility and total sperm motility and a nonsignificant correlation with age and sperm abnormal morphology. It is concluded that seminal mast cells decrease significantly in infertile men with Vx after surgical repair showing a significant negative correlation with sperm concentration, progressive sperm motility and total sperm motility.